Kaffir lime leaf extract mediated synthesis, anticancer activities and antibacterial kinetics of Ag and Ag/AgCl nanoparticles - Chaiyos Chankaew (2018)
© 2018 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences A facile phytosynthesis of Ag/AgCl and Ag nanoparticles (NPs) was developed using a crude water extract of Citrus hystrix DC (kaffir lime) leaves. The phytochemical and chloride contents of the extract, and various synthesis parameters were studied. The obtained Ag/AgCl and Ag NPs were of the cubic phase and mostly spherical in shape. Particle sizes of the yielded NPs were distributed in a narrow range with an average size of 20 and 38 nm for the Ag/AgCl and Ag NPs, respectively. The reducing function of the phytochemicals and the stabilizing ability of gelatin were demonstrated. The NPs showed significant anti-proliferative activities against the carcinoma HCT 116 and adenocarcinoma Caco-2 colorectal cell lines, but had a negative effect toward human fibroblasts. The NPs exhibited excellent antibacterial activities against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Bacillus cereus. The inactivation kinetics obtained in the presence of the NPs showed a biphasic behavior that can be explained by the Cerf model.